Dust reverberation mapping and light-curve modelling of Zw229-015. Issue 4 (13th September 2022) - Guise, E; Hönig, S F; Gorjian, V; Barth, A J; Almeyda, T; Pei, L; Cenko, S B; Edelson, R; Filippenko, A V; Joner, M D; Laney, C D; Li, W; et al.
ABSTRACT: Multiwavelength variability studies of active galactic nuclei can be used to probe their inner regions that are not directly resolvable. Dust reverberation mapping (DRM) estimates the size of the dust emitting region by measuring the delays between the infrared (IR) response to variability in the optical light curves. We measure DRM lags of Zw229-015 between optical ground-based and Kepler light curves and concurrent IR Spitzer 3.6 and 4.5 µm light curves from 2010 to 2015, finding an overall mean rest-frame lag of 18.3 ± 4.5 d. Each combination of optical and IR light curve returns lags that are consistent with each other within 1σ, which implies that the different wavelengths are dominated by the same hot dust emission. The lags measured for Zw229-015 are found to be consistently smaller than predictions using the lag–luminosity relationship. Also, the overall IR response to the optical emission actually depends on the geometry and structure of the dust emitting region as well, so we use Markov chain Monte Carlo modelling to simulate the dust distribution to further estimate these structural and geometrical properties. We find that a large increase in flux between the 2011–2012 observation seasons, which is more dramatic in the IR light curve, is not well simulated by a single dust component. When excluding this increase in flux, the modelling consistently suggests that the dust is distributed in an extended flat disc, and finds a mean inclination angle of 49$^{+3}_{-13}$ deg.